PENGARUH KEPEMIMPINAN BERKELANJUTAN TERHADAP EFEKTIVITAS ENVIRONMENTAL SUSTAINABILITY PROGRAM DI MADRASAH ALIYAH SWASTA KABUPATEN BOGOR - Ima Rahmawati; Hana Lestari; Titin Rustini; Anindya Puspa Kirana (Institut Agama Islam Sahid (INAIS) Bogor, 2026)
Environmental sustainability challenges require educational institutions to implement environmental sustainability programs in a planned and sustained manner, in line with the Ministry of Religious Affairs’ Priority Programs for strengthening environmentally oriented madrasahs. In Private Madrasah Aliyah, program effectiveness is strongly influenced by sustainable leadership in integrating sustainability principles into policies, organizational culture, and educational practices. This study aims to analyze the effect of sustainable leadership on the effectiveness of environmental sustainability programs in Private Madrasah Aliyah across Bogor Regency. A quantitative approach with a survey method was employed, involving 314 teachers selected through proportionate stratified random sampling from a population of 1,439 teachers. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares. The results indicate that sustainable leadership has a positive and significant effect on the effectiveness of environmental sustainability programs (β = 0.63; p < 0.001). These findings highlight the importance of strengthening sustainable leadership as a madrasah policy instrument to support the Ministry of Religious Affairs’ Priority Programs and to contribute to the achievement of SDG 4.7 and SDG 13.3.